Biopolitics as a Linguistic Problem in Philosophy of Giorgio Agamben - Valantiejūtė, Lina; Šerpytytė, Rita (Problemos, 2016)
The purpose of this paper is to show that the interpretation of biopolitics as developed by Giorgio Agamben is based, first of all, on the assumption of primacy of the language as ontologically negative structure. The crucial link between biopolitics and language in philosophy of Agamben shows up as fundamentally radicalized interpretation of the movement of negation in the Hegelian dialectics. According to Agamben, Hegelian sense-certainty is simultaneously negated by language and suspended in language in a form of unspeakability – pure negativity. Moreover, any social structure is formed in the same way, and this is the reason why any kind of politics for Agamben is already biopolitics. This insight allows us to formulate the conceptual analogy between the way Hegelian sense-certainty “exists” in language and man, as a living being, “exists” in politics – that is, as always suspended, negated but never fully removed.
Keywords: Agamben; biopolitics; Hegel; language; negativity